Tune in : - Jones, Matt (Oxford University Press, 2007)
Tune In is three-level listerning series for students of American English. The goal of this series is to teach students the two important aspects of listening: understanding what people say and how they say it. Teaching students to understand what people say focuses on listerning as acquisition.